Periodontitis Gingival Tissue Exosomes Cross and Compromise Human BBB in an In-Vitro 3D Model - Tigerwin Yang; Ranya Elsayed, PhD MBA (Elsevier, 2024)
OBJECTIVES: The objective of this aim was to test the hypothesis that human gingival EXO from PD patients (PD-EXO) promote BMEC dysfunction and increase BBB permeability by degrading tight junction proteins, using a human in-vitro 3D BBB model. METHODS: EXO purified from human gingiva (n=7) of stage III-IV, grade A/B PD (PD-EXO) and healthy subjects(con-EXO) (n=5) were characterized by NTA, TEM, WB, and multiplexed bead-based flow cytometry. DiI prelabeled PD-EXO or con-EXO and FITC dextran were added simultaneously to the luminal side (endothelial cells) of an in-vitro human 3D model of BBB (Neuromics,USA) and the media in the abluminal side (astrocytes and pericytes) was sampled for fluorescent measurement by plate reader at 0.5,4 and 24 hrs post-treatment. TEER was measured and tight junction proteins were examined using qPCR. RESULTS: IL-1β and IL-6 were expressed in PD-EXO while not detected in con-EXO. PD-EXO significantly decreased TEER measurements at 0.5, 4, and 24 hrs post-treatment while FITC and DiI EXO fluorescent signals in the lower compartment (abluminal side) of the BBB were significantly increased with PD-EXO relative to con-EXO. Furthermore, there was a significant downregulation of tight junction mRNA gene expression claudin-1 and -4 in BBB BMECs with PD-EXO. CONCLUSIONS: Using an in-vitro 3D model of BBB, our study illustrates that gingival EXO from PD patients could cross BBB and play a significant role in mediating a damaging effect on recipient BMECs of the BBB compromising its integrity. This suggests a novel mechanism of oral microbially induced EXO for AD risk. IMPLICATIONS: These findings shed light on the possible mechanism behind the association between periodontitis and alzheimer's disease.